Enterprise risk management and value creation: A literature review - KERRAOUS, El mehdi (Revue du contrôle, de la comptabilité et de l’audit, 2020)
Companies are under intense pressure from their shareholders to adopt a global and organized approach to manage risks, namely the enterprise risk management (ERM). However, the effect of ERM’s integration on the shareholders’ value creation is unclear. We have, on the one hand, the researchers who consider that this process creates shareholders’ value; on the other hand, we have the modern portfolio theory, which considers that ERM can destroy the shareholders’ value. Consequently, several empirical works test these hypotheses empirically. This article presents a literature review of these studies.